Rapid and cost-effective colorimetric detection of alkaloids in botanical extracts using a novel protocol with compressed tablets - Atteqa Safdar; Sara Iftikhar; Mouguissou Karim; Rashid Khan; Muhammad Qasim Hayat; Tayyaba Afsar; Ali Almajwal; Houda Amor; Suhail Razak (Scientific Reports)
Abstract In this study, a novel, cost-effective testing tablet was developed for the rapid detection of alkaloids in botanical extracts, herbal formulations, and pharmaceuticals. The relevant chemicals, including alkaloids, were successfully pressed into tablets using dry pressing molding technology. These chemicals were tested with mercury chloride, Potassium Iodide, Picric acid, Iodine, and Magnesium Stearate. Three separate water-soluble tablets were formed to produce respective reagents A, B, and C. The in vitro physicochemical properties of alkaloid testing tablets were established using XRD, FTIR, hardness, and dissolution tests. Additionally, the Botanical samples used to detect the alkaloidal presence were confirmed through literature and GC-MS analysis. Cymbopogon Citratus (Lemon Grass), Stevia Rebaudiana (Stevia), Curcuma Longa (Turmeric), Hippophae Rhamnoides L. (Sea Buckthorn seeds), Caffeine (Panadol Extra), Mentha Piperita (Menthol) leaves were utilised as botanical samples of alkaloidal contents, while water was used as a blank, along with Amodiaquine (Basoquin) as an anti-malarial drug registered by Pfizer as a positive control for the colorimetric testing and comparison of the results. The results showed that the chemical constituents of the tablets were intact, along with the integrity of the chemical testing, respective mechanical strength, and a good shelf life of a year. The proposed water-soluble tablets for the identification of alkaloids in samples of plant sources and pharmaceutical drugs have developed considerable colorimetric detection results and displaying good mechanical strength and stable physicochemical properties which demonstrated their potential application in the field of concerned pharmaceutical, nutraceuticals, and herbal manufacturing, and food processing industries in maintaining the quality and standards of the products.